(untitled) (Journal of Geography and Environmental Management, 2018)
In article the questions connected with emergence of the Silk Road, revival of the trade highway between all participating countries of a route on the Great Silk Road consider. One of topical issues – promotion of historical and cultural heritage of the countries lying on the Great Silk Road considers. The main question on preserving and promoting of historical and cultural heritage of member countries reflects. The short analysis of history of the Great Silk Road carries out; the key moments of development of historical and cultural tourism in the countries of a Silk Road are designated. The essence of work of the United Nations World Tourist Organization (UNWTO) and its cooperation with member countries of the Great Silk Road project is disclosed. Recommendations are made to create an image “Silk Road” as a viable tourist product.